Comparative Study of Soft Template on Gunningite Synthesis for Ibuprofen Adsorption Application - Maria Ulfa; Windi Apriliani (Indonesian Journal of Chemistry, 2023)
This study aimed to investigate the effect of soft template variations on Zinc Sulfate Hydrate (Gunningite) synthesis and the maximum adsorption capacity of ibuprofen. This study employed the soft template method and hydrothermal at 100 °C, followed by calcination at 550 °C. Here, ZnSO4 heptahydrate was used as the precursor for different templates. XRD analysis exhibited that the crystal sizes of Gunningite-F127G, Gunningite-F127, Gunningite-P123G, Gunningite-P123, and Gunningite-G were 18.35; 25.33; 25.67; 27.30; and 24.24 nm with crystallinity degrees of 36.89; 42.62; 46.83; 41.27; and 40.62%, respectively. FTIR examination indicated that the five samples contained functional groups of OH stretching at 3170 cm–1, Zn-O-Zn at 1637 cm–1, Zn-S=O symmetric and asymmetric at 900 and 1056 cm–1, and Zn-O at 521 cm–1. Furthermore, SEM-EDX investigation revealed that the morphology of all Gunningite samples was inhomogeneous due to agglomeration. Besides that, the elemental compositions in the samples were dominated by Zn and O elements. The maximum adsorption capacity obtained from each sample was 221.1 mg/g (Gunningite-F127G); 226.06 mg/g (Gunningite-F127); 234.23 mg/g (Gunningite-P123G); 229.76 mg/g (Gunningite-P123); and 222.85 mg/g (Gunningite-G). Moreover, the Gunningite kinetic model of ibuprofen adsorption followed Ho and McKay's pseudo-second-order kinetic model.